“How Are My Talk Moves?” Supporting Inservice Teachers Through Vertical Collaborative Coaching and Learning of Science Communities - Taylor, Joineé; Siegel, Marcelle (Innovations in Science Teacher Education, 2022)
Talk moves are dialogic pedagogical tools used to enhance purposeful discussion and support student learning. However, employing talk moves has proven challenging for some inservice teachers because they struggle with things like student participation and time. In this article, we describe a professional development program’s adaptation of professional learning communities to support a cohort of K–12 science teachers from different school districts in improving their teaching practice and effectiveness. We discuss the structure of the program and the use of collaborative reflection, and we also provide teacher reflection notes Specifically, we focus on one vertically integrated community, including elementary, middle, and high school teachers, who chose to focus on enhancing their pedagogical practice of talk moves. Ultimately, the teacher reflection notes revealed that being a part of such a community motivated them to enhance their teaching practices, boosted confidence, and also provided them networking opportunities with other teachers.